LINGUISTIC ANALYSIS OF THE EXPRESSIONS OF VERBAL BULLYING IN SELECTED SECONDARY SCHOOLS IN MACHAKOS SUB-COUNTY - MUTUNGA, DOROTHY KATUNGE (MksU Press, 2023)
The study aimed at analyzing linguistic expressions of verbal bullying and its harm on students in selected public schools in Machakos sub-county, Kenya. Bullying is a worldwide problem in schools and can have detrimental effects on those children involved; however, little has been done to uncover forms and impact of verbal bullying in secondary schools in Kenya. Therefore, the study sought to find out evidence of linguistic expressions used in verbal bullying and the forms they take, describe the linguistic meanings of the verbal bullying expressions and analyze their effects on the behavior of the targeted students with an aim of mitigating their effects. The study used the descriptive qualitative design method in data collection and analysis. Machakos Sub County has a population of 60 public and private secondary schools. The study collected data in public schools only due to time limitation. Out of an approximate sample of forty six public schools, purposive sampling was used to select schools based on their categories as follows: one sub-county mixed day school, one county mixed day and boarding school, one extra-county girl’s boarding school and one extra - county boy’s boarding school. Students were selected randomly from each category of school with two students from form one to form four randomly picked. A total of sixteen students were selected to form the population of the respondents. The students were interviewed to collect data. Apart from the students, the teachers who were in-charge of discipline and guidance and counselling were also involved in selection of the students who were interviewed. Other tools of data collection used were observation checklist and an audio-recorder. The collected data was transcribed, sorted and grouped into linguistic forms of verbal bullying using Politeness theory and the Speech Act theory. This study found out that verbal bullying expressions such as accusations/criticisms, contempt/ridiculing, evaluations, insults, slanders / spreading rumors, challenges, interruptions/intrusion, reminders and issuing orders were used by the perpetrators against the victims. Again, the study established that verbal bullying expressions had adverse effects on the targeted. Some reported to have felt isolated from the affiliated groups; others said they felt dejected, devalued, humiliated, embarrassed, withdrawn, low self-worth and helplessness. The study suggests that, learners should be taught the importance of using more polite language in their interactions and that expressions of verbal bullying should be exposed fully. The study identified verbal bullying expressions using face threatening acts as one of the tenets of the Politeness theory. Other studies could be conducted using its other tenets like the face saving strategies (Brown and Levinson, 1967) in a school set up. It can also be carried out in the national schools in administrators and the teaching staff on how best language can be used to enhance effective administration and productivity in a school set up. In conclusion, the issue of bullying is a menace to the student world and the society at large.